Effect of fungicides and Trichoderma harzianum on sclerotia of Sclerotium rolfsii - Oihabi, Abdellah; Ezzahiri, Brahim; Louali, Latifa; Khattabi, Naima (Phytopathologia Mediterranea, 2001)
The effect of three fungicides (benomyl, hymexazol, oxyquinoleine) on the viability of sclerotia of Sclerotium rolfsii was tested in natural and sterilized soils. A similar test was carried out in natural soil combining each of these fungicides with one of four isolates of Trichoderma harzianum. In addition, the mycelial growth of the T. harzianum isolates and S. rolfsii was monitored on agar media amended with these fungicides at three concentrations. Benomyl reduced the antagonistic ability of the T. harzianum isolates in the soil, oxyquinoleine yielded variable results, while hymexazol improved the antagonism of T. harzianum isolates. In an agar medium, benomyl inhibited all T. harzianum isolates, as did oxyquinoleine. By contrast, hymexazol had only a negligible effect on the growth of the antagonist.